Triggering phase disengagement of 1-alkyl-3-methylimidazolium chloride ionic liquids by using inorganic and organic salts. (September 2015) - Torres-Plasencia, Gustavo; Gutiérrez-Arnillas, Esther; Deive, Francisco J.; Ángeles Sanromán, M.; Rodríguez, Ana
Highlights: Alkylimidazolium-based ionic liquids are salted out by organic and inorganic salts. Empirical equations suitably correlate the experimental solubility data. Na2 CO3 is the salt providing greater immiscibility regions and salting out effect. Abstract: This study deals with the influence of different inorganic and organic salts made up with sodium, potassium and ammonium cations to induce phase segregation in aqueous solutions of C8 C1 imCl and C10 C1 imCl at T  = 298.15 K. The experimental solubility values are described by means of four empirical equations and the suitability of the models was analysed in the light of the standard deviation. The capability of the above mentioned salts to further phase de-mixing is discussed on the basis of their different molar Gibbs free energy of hydration (Δhyd G ), molar entropy of hydration (Δhyd S ) and pH. The efficiency of the separation was evaluated by determining the tie-lines, and these experimental values were fitted to three known models such as Bancroft, Othmer–Tobias and modified Setschenow equations.